Peranan Kepala Sekolah Sebagai Pemimpin Dalam Meningkatkan Mutu Pendidikan Di SMP Negeri 3 Kayuagung - Alhadi Yan Putra; Sri Wahyu Indrawati; Yuliana, Yuliana (CV. Ulil Albab Corp, 2025)
This study aims to find out and analyze the role of school principals as leaders in improving the quality of education at SMP Negeri 3 Kayuagung. This research was carried out at SMP Negeri 3 Kayuagung. This research was carried out from May to August 2024. The research object in this study uses a preliminary study, pre-field stage, field stage, data analysis stage and preparation stage. In this study, the researcher used qualitative research with a descriptive approach. In this study, the data collected are data that are in accordance with the focus of the research, namely about the role of school principals in improving the quality of education. The type in this study is divided into two parts, namely primary data and secondary data. The sampling technique used in this study is purpose sampling. The data collection technique in this study uses interview and documentation techniques. The data validity technique used by the author uses the data triangulation technique, namely by comparing data obtained through observation, interview, and documentation methods. The data analysis technique uses interactive analysis. The results of this study are the leadership strategy of the principal in improving the quality of education at SMP Negeri 3 Kayuagung is carried out well, namely: a) Direct coaching to see the quality of teachers at SMP Negeri 3 Kayuagung, b) monthly meetings to discuss improving the quality of teachers at SMP Negeri 3 Kayuagung, c) Teacher Working Group (KKG) d). providing motivation to teachers, e) giving awards to teachers, f) further study. The Principal of SMP Negeri 3 Kayuagung has conducted direct coaching to see the quality of teachers at SMP Negeri 3 Kayuagung has an influence on the progress and retreat of the school led both because it affects teachers and the teaching and learning process that takes place every day of the principal.